Implementation of Low-level Driver Interface for A CPU Card - Feng Luo; Fengjian Hu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In order to develop an automotive digital tachograph, a Central Processing Unit Card (CPU Card) interface IC is designed and implemented. The purpose of this paper is to present a driver proposal on the basis of a CPU card interface IC NCN6804. Under the platform of a Freescale’s microcontroller MPC5607B, the low-level driver interface is detailed both in hardware and software.  The test result shows that this low-level driver proposal can meet the operation demands of CPU cards, and this method is effective, especially in automotive applications. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1909